Integrated reservoir characterization and modeling of carbonate build-up with depositional environment imprint in Central Luconia, Sarawak Basin, Malaysia / Ana Widyanita - Ana, Widyanita (2017)
The studied field for the research is carbonate buildup platform type Cycle IV/V Middle Miocene, which is located in Central Luconia Province, Sarawak Basin. The structure of carbonate build-up is four way dip closure elongated ENE-WSW direction. The objectives of the study are to perform integrated subsurface study of geology, geophysics, petrophysics and engineering data for reservoir characterization, emphasizing core description, rock types, lithofacies grouping and interpretation of depositional environment. This integrated study was used to populate spatial distribution of reservoir property modeling, diagenesis impact to the reservoir properties enhancement and volumetric calculation. The development of carbonate is combination of aggradational, retrogradational and progradational, which related to sea level. Based on stratigraphic sequence scheme using density-neutron logs, porosity-permeability contrast, eight reservoir zonation and three tight layers were identified. Three regional depositional sequence interpreted throughout carbonate buildup, which are Basal Transgressive Phase, Lower Buildup Phase and Upper Buildup Phase, which indicated by maximum flooding surface and subaerial exposures. Eight lithofacies were identified based on core description using Dunham, Embry and Klovan classification. The grouping of these lithofacies was used to interpret the environment of deposition settings. Back reef to lagoonal setting consists of packstone, grainstone, rudstone, bafflestone and framestone with average porosity of 23% and permeability of 63 mD. Reef apron to Reef Crest setting consists of floatstone, rudstone, framestone with average porosity of 30% and permeability of 523 mD. Reef Front setting consists of grainstone, floatstone, rudstone, bindstone with average porosity of 14% and permeability of 12 mD. Fore Reef to Off Reef setting consists of wackestone, packstone, grainstone with average porosity of 7% and permeability of 0.9 mD. The environment of deposition interpreted in cored-well was